SYNTHETIZATION AND CHARACTERIZATION LUMINESCENCE COLOR OF CARBON NANODOTS MADE OF VERMICELLI WASTE WITH CIE 1931 - Raden Wisnu Murti Sulaindra; Wipsar Sunu Brams Dwandaru (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2022)
This study aims to (1) characterize carbon nanodots (C-dots) made from vermicelli waste synthesized by oven and microwave methods and (2) determine the effect of the mass of C-dots on the results of the colors that fluoresce by C-dots made from vermicelli waste. . This research was started by drying vermicelli waste. Furthermore, the heating method is carried out using an oven and microwave. The C-dots sample obtained was dissolved in 10 mL distilled water with various C-dots masses (in g): 0.003, 0.010, 0.015, 0.020 and 0.025. The C-dots samples were then characterized using ultraviolet-visible (UV-Vis) spectroscopy to determine the absorbance peaks and characterized using X-ray diffraction (XRD) to determine the phase formed in the sample. Next, the C-dots sample is irradiated with a UV laser to determine its luminescence. The results of the luminescence were captured with a camera. The luminescence image obtained is then analyzed for its RGB data and converted into xy data. The results of the xy data were then placed into the CIE 1931 graph. UV-Vis testing on the samples showed absorbance peaks in the wavelength range of 200 nm – 300 nm which indicated the presence of core C-dots. The results of the XRD characterization showed that the carbon phase of the C-dots powder was amorphous. The luminescence of the C-dots solution produces a cyan color. The more mass of C-dots dissolved, the shorter the glow and the more diffuse the color. The longest luminescence with the narrowest luminescence color was obtained in the solution with the smallest mass of C-dots, namely: 0.003 g.